Hydrophilic non-precious metal nitrogen-doped carbon electrocatalysts for enhanced efficiency in oxygen reduction reaction. Issue 97 (14th October 2015) - Hao, Guang-Ping; Sahraie, Nastaran Ranjbar; Zhang, Qiang; Krause, Simon; Oschatz, Martin; Bachmatiuk, Alicja; Strasser, Peter; Kaskel, Stefan
Abstract : The role of surface hydrophilicity of non-precious metal N-doped carbon electrocatalysts is found to be positive in enhancing catalysis efficiency for oxygen reduction reaction. Abstract : Exploring the role of surface hydrophilicity of non-precious metal N-doped carbon electrocatalysts in electrocatalysis is challenging. Herein we discover an ultra-hydrophilic non-precious carbon electrocatalyst, showing enhanced catalysis efficiency on both gravimetric and areal basis for oxygen reduction reaction due to a high dispersion of active centres.